Fragment – fetysz – fotografia - Marianna, Michałowska (Instytut Sztuki Polskiej Akademii Nauk, 2006)
Michałowska considers the thesis that an affinity between film and photography should not be sought in the linear order of the technological development of the medium but in the recalling of images by memory. Victor Burgin’s text "The Remembered Film" and Roland Barthes’s "Upon Leaving the Movie Theatre" provide the inspiration for the article. Burgin and Barthes argue that films begin to be regarded not as a coherent narrative continuum but as a „sequence of images”. We are in the process of being “trapped by the image” whereas the viewer begins to perceive a scene recorded by the photographic or cinematic medium as if it were part of his own experience. Michałowska examines the cinematic and photographic realisations of found footage (films by Bill Morisson, Lewis Klahr, photos of Friedl Kubelka and Andrzej P. Bator). A counterpoint for these audiovisual productions is William Gibson’s novel "Pattern Recognition" (2003) about film clips circulating in the Net. Lacking narrative linearity, the video files become the source of search for identity of Net users. These examples lead to the conclusion that in modern culture, photography and film cease to constitute only a component of specific artistic practice. When absorbed by human memory, they serve to express individual experiences.
Keywords: fetish; photography; Roland Barthes; Victor Burgin